Pineapple Pomace as Replacement for Wheat Bran in a Practical Extruded Diet for Catfish (Clarias gariepinus) - Oluwafemi Babatunde Oduntan; Siyanbola Adewunmi Omitoyin; Sule Okanlawon Shakiru (Syiah Kuala University, 2022)
This study investigated the effects of extruded pineapple pomace diet on growth and apparent digestibility coefficient of catfish (Clarias gariepinus). Four dietary extruded treatments of pineapple pomace Control (0%), T1 (10%), T2 (15%) and T3 (20 %) were fed ad libitum to catfish (21.05±0.04 g) for 60days. The final weight (53.52 - 57.45 g), weight gain (31.98 - 35.88 g) and feed conversion ratio (1.26 – 1.38) were relatively increased, while treatments up to 15% of pineapple pomace inclusion showed better performance. Fish survival rate (90.32 - 96.78%) showed significant difference. There were no significant differences (P0.05) in carcass composition among different dietary treatments. Apparent digestibility coefficient for crude protein, crude fibre and ash were highest in T2 (15%) and T3 (20%). The results indicated that pineapple pomace flour can be an ingredient in catfish diet for up to 20%. Key words: extruded; growth; apparent digestibility coefficient; carcass; proximate.